0880 Sleep Quality Change After RFCA In Paroxysmal Atrial Fibrillation& Relation Of Sleep Stability To The Recurrence: 24-hour Holter-based Cardiopulmonary Coupling Analysis. (27th April 2018) - Kim, W; Na, J; Jang, W; Park, E; Choi, J; Choi, C; Kim, J; Kim, E; Rha, S; Park, C; Seo, H; Lim, H
Abstract: Introduction: Sleep instability is highly prevalent in patients with cardiovascular disease (CVD) and evidence supports a casual association of sleep instability with CVD. We investigate the impact of radio-frequency catheter ablation (RFCA) on sleep instability in patients with paroxysmal atrial fibrillation (pAF) and the effect of sleep stability on recurrence of atrial fibrillation. Methods: This retrospective observational study was performed in pAF patients who underwent RFCA between October 2007 and January 2017. Of the total 445 patients, 24-hr Holter study was performed in 218 patients before and 6 months after RFCA. Sleep stability was assessed by 24-hr Holter study using cardiopulmonary coupling (CPC) analysis. We compared CPC parameter (high-frequency coupling[HFC], low frequency coupling[LFC], very low frequency coupling[VLFC], narrow band[NB], broad band[BB]) before and after RFCA. Results: Sleep stability was significantly improved six-month after RFCA. HFC (marker of stable sleep) and VLFC (REM/wakefulness marker) was increased (29.84% to 36.15%, p<0.001, 26.20% to 28.76%, p=0.002, respectively) while LFC, unstable sleep marker, was decreased (41.25% to 32.13%, p<0.001) after RFCA. After multivariate Cox regression analysis, LFCpreRFCA<50.3% (hazard ratio 8.2; 95% confidence interval 1.88–36.06; P=0.005) were associated with AF recurrences during the follow-up period. Conclusion: Sleep quality was improved after RFCA in patients with pAF. Furthermore, the recurrence rate was significantly lower after RFCA in patient who had pre-RFCA sleep instability(LFC≥50.3%). These results suggest that RFCA can influence sleep quality and sleep quality assessment by analyzing routine 24-hr Holter study can be a predictable marker of recurrence after RFCA in patients with pAF. Support (If Any):